The best person (or machine) for the job: Rethinking task shifting in healthcare - van Schalkwyk, May Ci; Bourek, Aleš; Kringos, Dionne Sofia; Siciliani, Luigi; Barry, Margaret M; De Maeseneer, Jan; McKee, Martin (Health policy, 2020)
Globally, health systems are faced with the difficult challenge of how to get the best results with the often limited number of health workers available to them. Exacerbating this challenge is the task of meeting ever-changing needs of service users and managing unprecedented technological advances. The process of matching skills to changing needs and opportunities is termed task shifting. It involves questioning health service goals, what health workers do, asking if it can be done in a better way, and implementing change. Task shifting in healthcare is often conceptualised as a process of transferring responsibility for 'simple' tasks from high-skilled but scarce health workers to those with less expertise and lower pay, and predominantly viewed as a means to reduce costs and promote efficiency. Here we present a position paper based on the work and expertise of the European Commission Expert Panel on Effective ways of Investing in Health. It contends that this is over simplistic, and aims to provide a new task shifting framework, informed by relevant evidence, and a series of recommendations. While far from comprehensive, there is a growing body of evidence that certain tasks traditionally undertaken by one type of health worker can be undertaken by others (or machines), in some cases to a higher standard, thus challenging the persistence of rigid professional boundaries. Task shifting has the potential to contribute to health systems strengthening when accompanied by adequate planning, resources, education, training and transparency.
Keywords: Health Workforce; zdravotničtí pracovníci; zdravotnický personál; poskytování zdravotní péče; Delivery of Health Care; Health Personnel; lidé; Health Facilities; zdravotnická zařízení; Humans